STRATEGIES TO OVERCOME FOREIGN LANGUAGE SPEAKING ANXIETY IN INDONESIAN EFL LEARNING CONTEXTS - Wijaya, Kristian Florensio (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
During the taxing L2 communicative enterprises undergone by Indonesian EFL learners, language teachers are heavily instigated to erect a more critical standpoint in picking up the most appropriate speaking learning approaches, strategies, and activities working best for the entire learners. This document analysis study was run to profoundly investigate 20 previous foreign language-speaking anxiety literature concerning the contributing factors and probable strategies that can potentially alleviate this psychological phenomenon. Two alleviating foreign language speaking anxiety strategies were proposed as follows: (1) The internalization of more innovative L2 speaking learning activities and (2) The existence of more enjoyable L2 speaking learning circumstances. At the end of the subsection, the researcher expectantly hoped prospective Indonesian EFL speaking learning experts, practitioners, policy-makers, and educationalists to promote a more positive speaking classroom atmosphere, constant speaking learning guidance, and various contextual speaking learning materials to progressively minimize learners’ foreign language speaking anxiety as well as foster their L2 communicative competencies into a greater level.